Effects of individual and combination treatment of azithromycin and doxycycline on U87 malignant glioma cell line - Hassan, Siti Nazihahasma (2024)
Glioblastoma (GBM) is the most prevalent malignant primary brain tumour in adults. Conventional treatment, which includes concurrent temozolomide (TMZ) chemotherapy and radiotherapy, provides only marginal survival benefits. Resistance to these therapies is both common and anticipated. Given the compelling evidence that azithromycin (AZI) and doxycycline (DOXY) induce apoptosis-related cytotoxicity in various cancer models in vitro and in vivo, these drugs were chosen for the present study. Their anticancer potential, both alone and in combination, was evaluated using the U87 malignant glioma cell line, specifically GBM. This in vitro study assessed cell viability, colony numbers, cytotoxic interactions, cell cycle distributions, nuclear morphology, cell death fractions, cytochrome C levels, and gene expression related to cytotoxicity and apoptosis. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that AZI (IC50: 92.0 µg/ml) exhibited greater potency compared to TMZ (IC50: 151.0 µg/ml) and DOXY (IC50:147.0 µg/ml) in U87 cells. Compared to single-drug treatments, AZI+DOXY (92.0+147.0 µg/ml) did not show increased cytotoxicity across various concentrations and time points, and evidence indicated an antagonistic interaction. Based on the cell survival assay, AZI exhibited a statistically significant antiproliferative effect compared to the negative control (NC) and DOXY, but only to NC under TMZ. Flow cytometric analysis using propidium iodide (PI) labelling revealed that AZI did not interfere with the cell cycle, whereas TMZ and DOXY or AZI+DOXY arrested cells in the S/G2/M and G0/G1 phases, respectively. Hoechst 33342 staining revealed apoptotic features in cell nuclei across all treatment groups; however, a larger nuclear area was observed than that of NC. Furthermore, flow cytometric analysis using Annexin V/PI labelling indicated that apoptosis was the predominant form of cell death induced by TMZ and AZI. In contrast, DOXY and AZI+DOXY induced both apoptosis and necrosis. Spectrophotometric analysis of cytochrome C protein levels exhibited an increase across all treatment groups. At the transcriptional level, all treatments enhanced TP53 and NFκβ1 mRNA expression levels, with AZI+DOXY significantly inducing both genes. PRKDC levels markedly increased with TMZ, DOXY, and AZI+DOXY. In contrast, γH2AX levels were higher in the AZI group than in any of the other treatments. DRP1 and MFN2 mRNA expression levels were elevated across all treatment groups, with AZI+DOXY substantially induced MFN2. Moreover, only AZI enhanced both BAX and BAK levels, whilst BCL2 significantly increased in the AZI and AZI+DOXY groups, and AZI+ DOXY showed the lowest BCLXL levels among the treatment groups. Additionally, AZI increased the ratios of BAX/BCL2, BAK/BCL2, and BAX/BCLXL, whereas AZI+ DOXY exhibited the highest ratio of BAK/BCLXL. In short, AZI shows anticancer activity by inhibiting cell proliferation, in part through the induction of apoptosis. On the other hand, DOXY and AZI+DOXY induce cell cycle arrest and both apoptosis and necrosis as part of their anticancer mechanisms. However, the experimental drugs appear to yield optimal anticancer effects when given alone rather than concurrently.